Tropicacosmos: Interseções estéticas a partir da música de Caetano Veloso e do cinema de Glauber Rocha - Marcos Sarieddine Araujo (2014)
Based on the affirmation made by Caetano Veloso in his book Verdade Tropical (1997), claiming that he understood his Tropicalia mission when he watched Glauber Rochas film Terra em Transe (1967), this research begins with a broad approach to the aspects associated with Tropicalia that go beyond the movement itself and can be found in other media, such as film and literature. Beginning the dissertation with a literature review, the study highlights and describes the aspects of the Tropicalia movement that seem to be the most relevant, specially Caetano Veloso's tropicalism: its role within Brazilian Popular Music (MPB) with regard to dissolving borders and including musical genres that initially were deemed to be its opposite; its political position with regard to the Cold War context of the 1960s; and the musical influences that would lead to the emergence of the movement and the consequent implications on Tropicalist music. Lastly, the study analyzes and reviews an aesthetic with which the artists involved in the Tropicalia movement in 1967/1968 considered to be a continuation of it: Oswald de Andrades anthropophagy. Here, the study seeks to reflect on its main artistic, aesthetic, and philosophical influences, especially Nietzsches stance on traditional Western thought, and to illustrate the similarities and differences between anthropophagy and Tropicalism. Finally we will analyze and revise an aesthetic with which the artists involved in Tropicalia movement 1967/1968 considered themselves to it followers: the antropofagia (anthropophagie) of Oswald de Andrade. We will try to investigate further what it is, their artistic, aesthetic and philosophical influences, especially Nietzsche's stance on the Western tradition of thought and will raise similarities and differences between cannibalism and tropicalism, specially in the year of 1967. Through this long journey, the study sought to create a more complex and profound image of this movement, which came about to claim that everything in music is possible and to show that borders, built to separate people into groups, are always artificial constructs. The study contributes with a discussion on Tropicalism and a discovery of very different universes that are similar without having to give up their own differences.